2013
DOI: 10.1164/rccm.201304-0676oc
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Carbon Monoxide Associated with Reduced Risk of Hospital Admissions for Respiratory Tract Infections

Abstract: Short-term exposure to ambient CO was associated with decreased risk of hospital admissions for RTI, suggesting some acute protective effects of low ambient CO exposure on respiratory infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 26 publications
3
46
1
Order By: Relevance
“…The present study demonstrates that hookah and cigarette smoke elevate indoor CO levels, but significantly more so with hookah smoke, resulting in CO levels several folds greater than the cigarette smoke and control concentrations. CO has been implicated to play a major role in a multitude of cardiovascular and airway diseases, including atherosclerosis,36 37 cardiomyopathy,38 chronic obstructive pulmonary disease,39 respiratory infections,40 asthma41 and cystic fibrosis 42. CO poisoning after hookah smoking has already been found in a number of case reports, with users presenting carboxyhaemoglobin levels 34% higher than normal after hookah use,43 44 syncope45 and confusion 46.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates that hookah and cigarette smoke elevate indoor CO levels, but significantly more so with hookah smoke, resulting in CO levels several folds greater than the cigarette smoke and control concentrations. CO has been implicated to play a major role in a multitude of cardiovascular and airway diseases, including atherosclerosis,36 37 cardiomyopathy,38 chronic obstructive pulmonary disease,39 respiratory infections,40 asthma41 and cystic fibrosis 42. CO poisoning after hookah smoking has already been found in a number of case reports, with users presenting carboxyhaemoglobin levels 34% higher than normal after hookah use,43 44 syncope45 and confusion 46.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, epidemiological studies on effects of CO on respiratory morbidity resulted in different findings (Tian et al, 2013). Some authors described significant increases of numbers of hospital admissions (Luginaah et al, 2005;Zanobetti and Schwartz, 2006).…”
Section: Comentioning
confidence: 99%
“…Some authors described significant increases of numbers of hospital admissions (Luginaah et al, 2005;Zanobetti and Schwartz, 2006). Other authors found small but significant effects of CO on respiratory hospitalizations (Fusco et al, 2001;Hinwood et al, 2006;Sauerzapf et al, 2009), could also not see significant effects (Fung et al, 2006), or detected protecting effects of CO for respiratory tract infections at lower concentration levels (Tian et al, 2013).…”
Section: Comentioning
confidence: 99%
“…Our findings supported recent ecological studies using the time-series design, which demonstrated respiratory benefits in association with a short-term exposure to ambient CO. For example, a time-series study in Hong Kong showed that shortterm exposure to ambient CO was associated with a decreased risk of hospital admission for respiratory tract infections (Tian et al, 2013). Another study in this city demonstrated the negative association between ambient CO and hospital admissions for COPD, and this association became stronger after adjustment for NO 2 or PM 2.5 (Tian et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, however, there is increasing controversy on whether acute exposure to ambient CO, usually at a low level, is hazardous on respiratory health. For example, three ecological time-series studies in Hong Kong and Shanghai, China reported reduced risks of respiratory disease hospitalizations in association with an acute CO exposure (Cai et al, 2015;Tian et al, 2014Tian et al, , 2013, suggesting that ambient CO might be an agent related with lower risks of respiratory diseases or symptoms.…”
Section: Introductionmentioning
confidence: 99%